2016
DOI: 10.1016/j.carbon.2015.10.084
|View full text |Cite
|
Sign up to set email alerts
|

The shear fracture toughness, K, of graphite

Abstract: The critical shear stress intensity factor, K IIc , herein referred to as the shear fracture toughness, K IIc (MPa√m), of two grades of graphite are reported. The range of specimen volumes was selected to elucidate any specimen size effect, but smaller volume specimen tests were largely unsuccessful, shear failure did not occur between the notches as expected. This was probably due to the specimen geometry causing the shear fracture stress to exceed the compressive failure stress. In subsequent testing the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…However, in the PFC simulation, the intact bonds between particles before cracking may prevent the pore compaction [24]. Interestingly, similar to the previous studies [5,6,15], the axial compression force fluctuates near the peak. These fluctuations may relate to the shear crack propagation and the stress evolution in the shear process and deserve further investigation.…”
Section: Numerical Results and Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, in the PFC simulation, the intact bonds between particles before cracking may prevent the pore compaction [24]. Interestingly, similar to the previous studies [5,6,15], the axial compression force fluctuates near the peak. These fluctuations may relate to the shear crack propagation and the stress evolution in the shear process and deserve further investigation.…”
Section: Numerical Results and Discussionsupporting
confidence: 73%
“…For example, Rao et al [4] conducted shear-box tests to determine the Mode II crack toughness and proposed that effective K IIC decreases with the increase of both the specimen thickness. Timothy and Don [5] applied double-edge notched compression specimens to determine the Mode II fracture toughness and found that the ratio of K IIC to K IC (tensile fracture toughness) is ∼1. 6.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental method used to test the Double Edge Notch Compression (DENC) specimens was the same as that used in our previous testing 13, 14 of identical geometry DENC specimens.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Sun et al 41 measured the ratio of K IIc / K Ic of anisotropic shale to be between 3 and 4 by shear‐box test, i.e., the value of K IIc is obviously larger than K Ic . Burchell and Erdman 50 measured the ratio of K IIc / K Ic of graphite to be about 1.6. AI‐Shayea et al 51 measured the ratio of K IIc / K Ic for sandstone specimens to be 2.14 to 2.19 under the condition of indoor temperature without confining pressure, the K IIc / K Ic to be 1.25 to 1.39 under the condition of 28 MPa confining pressure, and the K IIc / K Ic is 1.92 under the condition of 116°C indoor temperature.…”
Section: Introductionmentioning
confidence: 99%